Integrating sustainability indicators in Malaysia with Maqasid al-Shari'ah (the objectives of Islamic Law) - Ahmad Sarkawi, Azila; Abdullah, Alias; Md Dali, Norimah; Salim, Nurul Aida (2015)
Sustainability planning is not in isolation of Islam. Islam laid down some basic principles like the earth was created for human sustenance in due balance and proportion. Therefore it is human obligation to fulfil current and future human needs through proper planning and to prohibit mischief that will backlash on humanity itself. Above all, Islam advocates planning practices as manifestation of human roles as khalifah on earth tied with values and ethics. Underlying the human roles as khalifah, al-Quran and al-Sunnah set a value system in which their ultimate aim is to preserve the five human essentials namely faith, life, intellect, lineage and property. These five essentials are exegesis of all Quranic verses and Sunnah of the Prophet called Maqasid al-Shari’ah. Thus, the paper reports an attempt to integrate the five essentials of Maqasid al-Shari’ah with the MURNInet (The Malaysian Urban Indicators Network) sustainability indicators. A survey was carried out on 86 desk-officers at the selected Local Planning Authorities namely Majlis Bandaraya Shah Alam, Majlis Perbandaran Bentong and Perbadanan Putrajaya together with their respective State Town and Country Planning Department, by virtue of their achievement as the most sustainable cities within the period 20082010. Within the eleven sectors of MURNInet, the result showed that five sectors scored the highest percentage in terms of their relation with the preservation of faith, three sectors on preservation of self, and one sector each on preservation of intellect, lineage and property. Through a Focus Group Discussion, the study validates the concept of sustainability in Islam derived from various Islamic injunctions in comparison with the contemporary concept of sustainability. At the end, the study managed to establish a sustainability concept perceived in Islam and its relation with the contemporary sustainability indicators in Malaysia.